Minimum wage order: the effect on the increment of the minimum wage in Malaysia / Nur Zatul Miza Mohd Zamri and Nor Ajwa Mohamad Sanusi - Mohd Zamri, Nur Zatul Miza; Mohamad Sanusi, Nor Ajwa (2022)
The increase in the minimum wage is being discussed by all Malaysians, especially among employers, employees and traders. Last May, the government set a new minimum wage for 16 city councils and 10 municipalities. This increase could provide opportunities to those affected especially during the Covid-19 pandemic and increase the ability of the people to bear their cost of living and improve existing financial problems. According to Sofea Azahar (2021), Mean household expenditure increased by 4% during the 2016-2019 period. Among all expenses, food and beverage accounts for the biggest portion at 17.3% and within the income groups, B40 households allocate a high share of their expenditure on food compared to those in other income groups. This could prove that before the advent of Covid-19 again low-income people had worrying financial problems as the existing salaries could not afford the high cost of living. However, there are also parties who will bear the loss from this new stipulation. Therefore, the purpose of this study is to know and identify the issue of the minimum wage in Malaysia before and after the announcement of the minimum wage increase. In addition, this study was also conducted to find out the minimum wage set in urban and rural areas by the government before and after the new minimum wage announcement whether it is appropriate and sufficient or will cause any problems. The proposed minimum wage, which would play a significant role in eliminating labour market inefficiencies and enhancing the social welfare of low-paid workers, would benefit up to one-third of the Malaysian workforce. Additionally, the rise might promote increased labour market participation and boost the economy's use of labour (Prashant, J. 2022).